Health related quality of life and associated factors after cesarean delivery among postpartum mothers in Gondar, Ethiopia: a cross-sectional study - Daniel Getaneh Damtie; Misganaw Mengie Workie; Mulualem Endeshaw Zeleke; Wubie Birlie Chekol (BMC Pregnancy and Childbirth)
Abstract Background Health-related quality of life following cesarean delivery can be compromised due to the physical, mental, and emotional impacts of surgery and anesthesia. Despite the critical nature of the postpartum period after cesarean delivery, it remains under-explored, with most studies focusing on vaginal deliveries and neglecting the unique challenges of cesarean recovery. Therefore, this study aimed to assess health related quality of life and associated factors after caesarean delivery among postpartum mothers in Gondar, Ethiopia. Methods A cross-sectional study was conducted in public health facilities of Gondar town using the Medical Outcomes Study Short Form-36. Data were collected from 424 postpartum women following cesarean delivery between April and June 2024 through face-to-face interviews, semi-structured questionnaires, and medical chart reviews. Simple random sampling was used, with participants proportionally allocated to each health facility. Data were entered into Epi-data version 4.6 and analyzed using SPSS version 25. Logistic regression models were applied to predict the health-related quality of life. Results Among 418 post caesarean deliveries, 278 (66.5%) had lower level of health-related quality of life. The mean scores of physical component summary, mental component summary and overall health related quality of life were found 48.22 ± 5.63, 47.62 ± 6.02 and 47.92 ± 4.28 respectively. Factors associated with lower overall health related quality of life were postnatal care less than two (AOR = 2.58, 95% CI = 1.59–4.19), pregnancy complications [AOR 5.32, 95% CI (2.69–10.54)], general anesthesia (AOR = 2.36, 95% CI = 1.08–5.14), perceived pain after discharge (AOR = 2.64, 95% CI = 1.61–4.35) and postpartum depression (AOR = 2.41, 95% CI = 1.22–4.77). Conclusion Two-thirds of postpartum mothers had low health related quality of life after cesarean delivery. Key factors included inadequate postnatal care, postpartum depression, anesthesia type, pregnancy complications, and perceived pain. We suggest that health care providers need to give particular attention to mothers during the perioperative period and increased postnatal care services to improve maternal well-being.